Climate change to the year 2000 : a survey of expert opinion - National Defense University; U.S Department of Agriculture (Washington : The University : [for sale by Supt. of Docs., U.S. Govt. Print. Off.], 1978)
The book attempted to quantify perceptions of global change to the year 2000 based on an interdepartmental study at The Defense University. A survey of 24 climatologists from seven countries was carried out to determine specified climatic events for the year 2000..
"Contract number MDA903-77-C-0914."
asm; 14/01/2019
Loans
Keywords: Climatic changes; Long-range weather forecasting